CHEMICAL WASTE MANAGEMENT IN EDUCATIONAL INSTITUTIONS - Magriotis, Zuy Maria; Saczk, Adelir Aparecida; Rosa, Isael Aparecido; Salgado, Hélvia Mara Ribeiro (UI Scholars Hub, 2021)
Green universities and Education for Sustainable Development have an important role in reaching a sustainable society. However, there is many gaps in this area. This study aimed to report the implementation and the results of the Chemical Waste Management Program (CWMP) of the Federal University of Lavras (UFLA). The CWMP have been implemented in 2009 to solve the existing environmental problem of inadequate disposal of chemical waste generated in UFLA’s laboratories. In order to carry out the CWMP actions, the Chemical Waste Management Laboratory (CWML) was created in 2009, with the function of collecting, treating, and giving a final destination to the chemical waste generated by UFLA’s teaching, research, and service laboratories. The treatments applied to chemical waste are adsorption, precipitation, distillation, drying and composting. Another important action of the CWMP was the realization of training courses and seminars, in addition to a graduate discipline, to raise awareness of the academic community about the importance of the correct disposal of chemical waste. The development of sustainable treatment methods, using recycled and low-cost materials allowed an increase of 400% in the amount of waste treated in the CWML. From 2009 to 2019, the CWML increased the number of solvents recovered from the waste and the amount of Chemical Waste Exchange (CWE). The CWMP contributed for UFLA to apply the concept of green chemistry daily. The results from these actions have contributed for the university to reach the second position among most sustainable universities in Latin America. Despite the increase in the amount of treated waste, it is necessary to develop new sustainable treatment methodologies to meet the university's growing demand.